State-of-the-art analysis of intrapreneurship: A review of the theoretical construct and its bibliometrics - Esthela Galván-Vela; Eduardo Arango Herrera; Deisy Milena Sorzano Rodríguez; Rafael Ravina Ripoll (Journal of Risk and Financial Management, 2021)
Business complexity demands that companies look for alternative ways to ensure their survival. Thus, one means to generate a competitive position, growth and development is intrapreneurship, which refers to entrepreneurship that arises within established organizations. However, current studies of the phenomenon are sometimes limited to contributions that lack substantive theory. Given this problem, the objective of this study was to determine the current state of the art of intrapreneurship based on a documentary analysis. Similarly, a bibliometric analysis was carried out that evaluated the existing publications. A total of 133 documents related to the term were found. After analyzing these documents, we concluded that new studies on the matter need to be developed. Therefore, a future agenda is proposed and the implications of this phenomenon on the performance of current companies are discussed.
Keywords: 330; bibliometric analysis; bibliometrics; corporate entrepreneurship; intrapreneurship; models